On-chip gradient generation in 256 microfluidic cell cultures: simulation and experimental validation1. Issue 15 (7th August 2015) - Somaweera, Himali; Haputhanthri, Shehan O.; Ibraguimov, Akif; Pappas, Dimitri
<x xml:space="preserve">Abstract</x> A microfluidic diffusion diluter was used to create a stable concentration gradient for dose response studies.